The lost history of the transistor. - Riordan, M.
Bell Labs is famous for inventing the transistor. But 50 years ago Texas Instruments unveiled the first commercial silicon transistors - launching the electronics industry on its meteoric rise.
Keywords: Bell Labs; Bell Telephone Laboratories; Texas Instruments; History; Junction transistor; Silicon transistors